MINIMALIST BIOPHILIC INTERIOR DESIGN AT DAYCARE IN JAKARTA - Agnes Putri Rhulina Br. Ginting; Lu'lu' Purwaningrum (TAMA: Journal of Visual Arts, 2024)
Daycare is a public facility that not many people know about or use currently. Even though daycare can be a support for parents who work and don't have a nanny. Even though several daycares have been established in Jakarta itself, the concept presented at this daycare is very different. The current condition of Jakarta, which is increasingly congested and air pollution is quite high, is one of the reasons for designing this daycare. Daycare is designed not only as a supporting facility, but as a place that can support children's development and growth. This design uses a biophilic minimalist concept, where this concept presents a natural concept combined with a minimalist concept that is suitable for children.